Structured populations, cell growth and measure valued balance laws - Carrillo, José Antonio; Colombo, Rinaldo M.; Gwiazda, Piotr (Journal of differential equations, 2012)
A well-posedness theory of measure valued solutions to balance laws is presented. Nonlinear semigroups are constructed by means of the operator splitting algorithm. This approach allows to separate the differential terms from the integral ones, leading to a significant simplification of the proofs. Continuous dependence with respect to parameters is also shown. The whole framework allows a unified approach to a variety of structured population models, providing to each of them the basic well posedness and stability results.
Available online 21 November 2011
Gesehen am 16.08.2017